Data supporting: 'Comparative analysis of ammonia combustion for domestic applications' - Bazooyar, Bahamin; Manovic, Vasilije; Nabavi, Seyed Ali (Cranfield University, 2022)
The research of ammonia combustion in Gas Turbines and Boilers
Keywords: 'Computational Fluid Dynamic'